Protoplast Fusion of Koji-Mold Aspergillus spp. to Improve Kecap Production - Sebastian Margino; F. S. Rejeki; E. S. Rahayu; D. Wibowo (Indonesian Food and Nutrition Progress, 1998)
Protoplast fusion of Aspergillus oryzae and A. niger for improving the enzyme productivity of desirable kojimolds for kecap (Indonesian soy sauce) was studied. Protoplasting of both mycellium aspergilli was obtained by treating them using Novozyme 234, at final concen tration 5 mg/ml and the time of exposure for three and two hours. Regenerated protoplasts of A. oryzae oncomplete medium (RCMMPA) was 1.46-3.74 % and on minimal medium (RMMPA) was 0.93-4.93%, whereas A. niger was 0.44-7.64 % and 0.17-6.25 %, respectively. Protoplast fusion was conducted in 30 % PEG 6000 (Polyethylene Glycol) containing 0.01 M CaC12 and 0.05 % glycine, and at pH 7.5. For selecting the suspected fusant Dinikonasol 12.5%, at the final concentration 200 ppm and Cycloheximide at the final concentration 100 ppm Was used as a marker. Results showed that hundred eighteen of suspected fusants were obtained and after screening found that seven as selected fusants. Based on the enzyme activities, finally, fusant number 77 was selected as a fusant with high proteolytic and glutaminase activities.